Chronic Pepsin Exposure Promotes Anchorage‐Independent Growth and Migration of a Hypopharyngeal Squamous Cell Line. (27th December 2013) - Kelly, Elizabeth A.; Samuels, Tina L.; Johnston, Nikki
Abstract : Outcome Objectives: (1) Investigate the role of reflux, specifically pepsin, in laryngopharyngeal carcinogenesis. (2) Evaluate effects of chronic pepsin exposure on cell migration, apoptosis, and colony‐forming ability in hypopharyngeal cells. Study Design: Translation research. Setting: Academic research laboratory. Methods: Human hypopharyngeal squamous carcinoma FaDu cells were chronically exposed to nonacidic pepsin (exposed for 24 hours, 4 times over 2 weeks at the following concentrations: 0.01 mg/mL, 0.1 mg/mL, or 1 mg/mL). Precise wounds were created in confluent cell plates, and rates of cell migration into wounds were quantified. Separately, cell viability of chronic pepsin‐exposed FaDu cells acutely treated with paclitaxel was measured. Finally, a clonogenic assay was performed on these cells to measure effects of chronic pepsin exposure on colony‐forming ability. Results: An increased rate of relative wound density was observed in chronic pepsin‐treated (0.01 mg/mL, 0.1 mg/mL) cells compared with control ( P <. 001), suggesting greater rates of cell migration. Pepsin‐treated (0.1 mg/mL) cells demonstrated on average greater cell viability compared with control after exposure to paclitaxel, suggesting possible apoptotic resistance; however, this was not statistically significant. Chronic pepsin exposure (0.1 mg/mL, 1 mg/mL) was associated with a dose‐dependent increase in colony‐forming ability relative to control ( P <. 001). Conclusion: Hypopharyngeal squamous cell line chronically exposed to pepsin demonstrated increased cell migration and colony‐forming ability relative to control cells. These experiments indicate that chronic pepsin exposure acts as a promoter of tumorigenesis and metastasis of airway epithelium, suggesting a role for pepsin in laryngopharyngeal carcinogenesis attributed to gastric reflux.